The Influence Of Competence And Accounting Information System On The Quality Of Bumdes Financial Report In West Kupang: The Role Of Governance As A Moderating Variable - Situmorang, Resvina; Sanga, Marianus Hendrilensio; Sogen, Skolastika Ananda Queen (SEAN Institute, 2024)
This study investigates the influence of competence and the use of accounting information system on the quality of financial reports in BUMDes (village-owned enterprises) in West Kupang District, while also examining governance as a moderating variable. The research employed a purposive sampling method, selecting 36 participants from all BUMDes in the district. Data were collected through questionnaires distributed via Google Forms and analyzed using the SEM-PLS (partial least squares) technique with Smart PLS 3 software. The results reveal that competence does not significantly affect the quality of financial reports, whereas the use of accounting information system has a positive and significant impact. Governance plays a moderating role, strengthening the relationship between competence and the quality of financial reports but weakening the relationship between the use of accounting information system and the quality of financial reports. These findings highlight the critical role of governance in enhancing financial reporting quality. The study's practical implications suggest the need for improved governance effectiveness and financial management strategies in village enterprises to ensure better financial reporting practices. These insights contribute to the literature on village financial management and provide actionable recommendations for policymakers and stakeholders.